BUILT ENVIRONMENT ROLE IN CHANGING MOTHERS PERCEPTION ON CHILDREN’S WALKING INDEPENDENTLY TO SCHOOL - Yong Adilah S Harumain; S Koting; NSA Sukor; Melasutra Md Dali; NF Hamzah; T Osada; FI Ruslan; NF Fauzi (Diponegoro University, 2022)
Women have a great significance in their children's lives from the moment they are born. The choice that mothers make regarding their children's mode of travelling to school will have a significant impact on how those children will think about walking and cycling in the future. The purpose of this study is to identify the perspectives of mothers towards allowing their children to school by walking in an area that is deemed suitable for such trip in our discussion on the nation’s future generation towards walking and not depending on private vehicles as the main mode of travelling. A focus group discussion, also known as FGD, took place in Taman Ilmu, which is in Nibong Tebal, Pulau Pinang. As a result of this study, using thematic analysis to analyse the results of conversation during the FGD session and collective mapping, we discovered four (4) themes of mother’s perspectives towards their children walking to school, which are as follows: (1) confidence and trust; (2) safety; (3) age and gender; and (4) weather. In summary, the built environment can be described as a solution to the 'out of control' scenario in which government and parental roles are effective in resolving the issue of children walking independently to school.